Responses of Phytoplanktonic Chlorophyll-a Composition to Inorganic Turbidity Caused by Mine Tailings - Nunes, Patrícia; Roland, Fabio; Amado, André M.; Resende, Nathália da Silva; Cardoso, Simone Jaqueline (Frontiers in Environmental Science, 2022)
Inorganic turbidity can limit light penetration in water and reduce phytoplankton photosynthesis. Anthropogenic activities such as mining can produce or augment the amount of suspended inorganic particles in water. Recent mining disasters in Brazil have released tons of mine tailings into aquatic ecosystems, with known and unknown negative consequences for aquatic life, biodiversity, and ecosystem services, beyond the human and material losses. Here, we investigated the effects of inorganic turbidity caused by sediments from two areas in Lake Batata, one natural and the other impacted by bauxite tailings, on phytoplankton chlorophyll content and composition. We experimentally compared the effects of different levels of turbidity (12, 50, and 300 NTU) caused by the addition of sediments from the two lake areas on a chlorophyll-a gradient (5, 15, and 25 µg/L). Inorganic turbidity did not consistently reduce chlorophyll-a concentrations. In treatments with high chlorophyll-a, high turbidity was associated with lower chlorophyll-a concentrations at the end of the experiment. On the other hand, in low-chlorophyll treatments, high turbidity was associated with higher chlorophyll-a concentrations. In treatments with sediments from the natural area, overall chlorophyll-a levels were higher than in treatments with sediments from the impacted area. Phagotrophic algae dominated in treatments with sediments from the impacted area (Chrysophyceae 34%, Chlorophyceae 26%, and Cyanobacteria 22% of total density) and in treatments with sediment from the natural area (Euglenophyceae 26%, Chrysophyceae 23%, and Chlorophyceae 20%). Our results increased understanding of how turbidity caused by both natural sediments and mine tailings can affect phytoplankton chlorophyll-a and its energetic impacts on freshwater ecosystems. We conclude that high turbidity does not lead to a reduction in chlorophyll-a concentrations and sediment from natural area allowed higher chlorophyll-a levels, indicating that impacted area sediment affected more phytoplankton.